2020
DOI: 10.5194/acp-20-3009-2020
|View full text |Cite
|
Sign up to set email alerts
|

Local and remote mean and extreme temperature response to regional aerosol emissions reductions

Abstract: Abstract. The climatic implications of regional aerosol and precursor emissions reductions implemented to protect human health are poorly understood. We investigate the mean and extreme temperature response to regional changes in aerosol emissions using three coupled chemistry–climate models: NOAA GFDL CM3, NCAR CESM1, and NASA GISS-E2. Our approach contrasts a long present-day control simulation from each model (up to 400 years with perpetual year 2000 or 2005 emissions) with 14 individual aerosol emissions p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 55 publications
4
24
0
Order By: Relevance
“…6). This result is consistent with recent studies showing high Arctic sensitivity to aerosol reductions (Acosta Navarro et al, 2016;Lewinschal et al, 2019;Westervelt et al, 2020). Other latitudinal bands also significantly warm, including the NH midlatitudes (30-60 • N), tropics (30 • S-30 • N), and Southern Hemisphere (SH) midlatitudes (60-30 • S) at 0.10 ± 0.03, 0.05 ± 0.01, and 0.03 ± 0.02 K decade −1 , respectively.…”
Section: Regional Climate and Air Quality Trendssupporting
confidence: 93%
“…6). This result is consistent with recent studies showing high Arctic sensitivity to aerosol reductions (Acosta Navarro et al, 2016;Lewinschal et al, 2019;Westervelt et al, 2020). Other latitudinal bands also significantly warm, including the NH midlatitudes (30-60 • N), tropics (30 • S-30 • N), and Southern Hemisphere (SH) midlatitudes (60-30 • S) at 0.10 ± 0.03, 0.05 ± 0.01, and 0.03 ± 0.02 K decade −1 , respectively.…”
Section: Regional Climate and Air Quality Trendssupporting
confidence: 93%
“…Aerosols give rise to both local and remote temperature responses, so that the geographic distributions of aerosol radiative forcing and temperature effects are largely dislocated (Shindell et al, 2010;Nordling at al., 2019). Furthermore, the same aerosol emissions originating from different regions vary in their climate forcing efficacies, with their global surface temperature response per unit global radiative forcing differing by factors of between 2 and 14, depending on aerosols species and the models used (Kasoar et al, 2018;Westervelt, et al, 2020;Persad and Caldeira, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The authors pinpointed the mixed results from the models to their different treatments of aerosol microphysical processes and aerosolcloud interactions. Westervelt et al (2020) also used three climate models (GFDL, CESM1, and GISS-E2) to investigate the surface temperature responses to the removals (or significant reductions) of aerosol sources from several different regions, including China and India. Overall, the models varied in aerosol radiative forcings and regional temperature response patterns associated with Asian aerosol reductions but suggested that the reductions mostly result in a significant surface temperature increase across the Northern Hemisphere and particularly over the Arctic.…”
Section: Introductionmentioning
confidence: 99%
“…Aerosol extinction of incoming solar radiation via direct and indirect effects results in weaker precipitation due to weakened circulation (Li et al, 2019;Ramanathan et al, 2001;Singh, 2016). Aerosol emissions and thus forcing are also spatially heterogeneous both zonally and meridionally, which can result in further enhancement of the circulation (dynamic) component of the precipitation response (Li et al, 2018;Shen & Zhao, 2020;Westervelt et al, 2017Westervelt et al, , 2018Westervelt et al, , 2020. Research has also shown that the fast response (using fixed SST) dominates the total aerosol-induced monsoon changes but that SST feedbacks are more important for the GHG-forced response (Li et al, 2018).…”
Section: Introductionmentioning
confidence: 99%